Valorization of Adhatoda vasica leaves: Extraction, in vitro analyses and in silico approaches - Rudrapal, Mithun; Vallinayagam, Sugumari; Aldosari, Sahar; Khan, Johra; Albadrani, Hind; Al-Shareeda, Alaa; Kamal, Mehnaz (Frontiers in Nutrition, 2023)
Adhatoda vasica (also called Vasaka) is a traditional medicinal herb used traditionally for the relief of cough, asthma, nasal congestion, bronchial inflammation, upper respiratory infections, bleeding disorders, skin diseases, leprosy, tuberculosis, diabetes, allergic conditions, rheumatism, tumor, and many more diseases. The present study aims to investigate the biological activities of vasicine, a potent alkaloid from A.vasica with different biological/ pharmacological assays and in silico techniques. Vasicine showed antimicrobial activity as evidenced fromthe colony-forming unit assay. It showed antioxidant activity in ABTS scavenging assay (IC50 = 11.5 μg/ml), ferric reducing power assay (IC50 = 15 μg/ml), DPPH radical scavenging assay (IC50 = 18.2 μg/ml), hydroxyl radical scavenging assay (IC50 = 22 μg/ml), and hydrogen peroxide assay (IC50 = 27.8 μg/ml). It also showed anti-inflammatory activity in proteinase inhibitory assay (IC50 = 76 μg/ml), BSA method (IC50 = 51.7 μg/ml), egg albumin method (IC50 = 53.2μg/ml), and lipooxygenase inhibition assay (IC50 = 76 μg/ml). Vasicine showed antidiabetic activity in α-amylase inhibition assay (IC50 = 47.6μg/ml), α-glucosidase inhibition assay (IC50 = 49.68μg/ml), and non-enzymatic glycosylation of hemoglobin assay.It showed antiviral activity against HIV-protease (IC50= 38.5 μg/ml). Vasicine also showed anticancer activity against lung cancer cells (IC50 = 46.5 μg/ml) and human fibroblast cells (IC50 = 82.5 μg/ml). In-silico studies revealed that similar to the native ligands, vasicine also showed a low binding energy, i.e. good binding affinity for the active binding sites and interacted with α-amylase (-6.7 kcal/mol), α-glucosidase (-7.6 kcal/mol), cyclooxygenase (-7.4 kcal/mol), epidermal growth factor receptor (-6.4 kcal/mol), lipooxygenase (-6.9 kcal/mol), and HIV-protease (-6.4 kcal/mol).The present study ascertains the potential of vasicine as a bioactive compound isolated from A. vasica having therapeutic usefulness in many diseases.